1, 4-Dioxane cosolvency impacts on trichloroethene dissolution and sorption. (September 2019) - Milavec, Justin; Tick, Geoffrey R.; Brusseau, Mark L.; Carroll, Kenneth C.
Abstract: Solvent stabilizer 1, 4-dioxane, an emerging recalcitrant groundwater contaminant, was commonly added to chlorinated solvents such as trichloroethene (TCE), and the impact of co-disposal on contaminant transport processes remains uncertain. A series of batch equilibrium experiments was conducted with variations of 1, 4-dioxane and TCE composition to evaluate aqueous dissolution of the two components and their sorption to aquifer sediments. The solubility of TCE increased with increasing amounts of 1, 4-dioxane, indicating that 1, 4-dioxane acts as a cosolvent causing solubility enhancement of co-contaminants. The solubilization results compared favorably with predictions using the log-linear cosolvency model. Equilibrium sorption coefficients ( K d and K f ) were also measured for different 1, 4-dioxane and TCE compositions, and the findings indicate that both contaminants adsorb to aquifer sediments and TCE K d values increased with increasing organic matter content. However, the K d for TCE decreased with increases in 1, 4-dioxane concentration, which was attributed to cosolvency impacts on TCE solubility. These findings further advance our understanding of the mass-transfer processes controlling groundwater plumes containing 1, 4-dioxane, and also have implications for the remediation of 1, 4-dioxane contamination. Graphical abstract: Image 10485 Highlights: Cosolvency impacts of 1, 4-dioxane co-disposal with chlorinated solvent TCE. 1, 4-Dioxane increases the TCE solubility and decreases sorption. Solubility enhancement was predicted using log-linear cosolvency model. Abstract : 1, 4-Dioxane (cosolvent) increased the solubility of TCE and decreases sorption, and log-linear cosolvency model predicted solubility enhancement.